Между ченнелингом, публицистикой и художественным нарративом (на матенриале произведения Даниила Андреева „Роза Мира”) - Бацевич, Флорий (Studia Rossica Posnaniensia, 2015)
This article considers certain functional and communicative distinctive features of interdiscursiveness, which is understood as an information flow phenomenon, based on the outstanding work The Rose of the World by the Russian writer and philosopher Daniil Andreev. Certain distinctive features of this book that are characteristic of channeled messages, philosophical and religious treaties, literary discourse, and publicistic works were singled out here by taking into consideration such categories as the textual modus, linguistic modality, the addresser’s model and others.